Revisiting multi-omics-based predictors of the plasma triglyceride response to an omega-3 fatty acid supplementation - Morin-Bernier, Josiane; de Toro-Martín, Juan; Barbe, Valentin; San-Cristobal, Rodrigo; Lemieux, Simone; Rudkowska, Iwona; Couture, Patrick; Barbier, Olivier; Vohl, Marie-Claude (Frontiers in Nutrition, 2024)
The aim of the present study was to identify the metabolomic signature of responders and non-responders to an omega-3 fatty acid (n-3 FA) supplementation, and to test the ability of a multi-omics classifier combining genomic, lipidomic and metabolomic features to discriminate plasma triglyceride (TG) response phenotypes.Methods: A total of 208 participants of the Fatty Acid Sensor (FAS) Study took 5g per day of fish oil, providing 1.9-2.2g eicosapentaenoic acid (EPA) and 1.1g docosahexaenoic (DHA) daily over a 6week period, and were further divided into two subgroups: responders and non-responders, according to the change in plasma TG levels after the supplementation. Changes in plasma levels of 6 short-chain fatty acids (SCFA) and 25 bile acids (BA) during the intervention were compared between subgroups using a linear mixed model, and the impact of SCFAs and BAs on the TG response was tested in a mediation analysis. Genotyping was conducted using the Illumina Human Omni-5 Quad BeadChip. Mass spectrometry was used to quantify plasma TG and cholesterol esters levels, as well as plasma SCFA and BA levels. A classifier was developed and tested within the DIABLO framework, which implements a partial least squares-discriminant analysis to multi-omics analysis. Different classifiers were developed by combining data from genomics, lipidomics and metabolomics. Results: Plasma levels of none of the SCFAs or BAs measured before and after the n-3 FA supplementation were significantly different between responders and non-responders. SCFAs but not BAs were marginally relevant in the classification of plasma TG responses. A classifier built by adding plasma SCFAs and lipidomic layers to genomic data was able to even the accuracy of 85% shown by the genomic predictor alone.These results inform on the marginal relevance of SCFA and BA plasma levels as surrogate measures of gut microbiome in the assessment of the interindividual variability observed in the plasma TG response to an n-3 FA supplementation. Genomic data still represent the best predictor of plasma TG response, and the inclusion of metabolomic data added little to the ability to discriminate the plasma TG response phenotypes.